PERHITUNGAN SUBSIDI PUPUK 2004 BERDASARKAN ALTERNATIF PERHITUNGAN SUBSIDI ATAS BIAYA DISTRIBUSI - MAULANA, MOHAMAD (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006)
Economic crisis was decreasing farmer income. At the end, its would be difficult for the fertilizer producers to stabilized production for domestic supply. For stabilizing fertilizer production and price, it is necessary to government to subsidized fertilizer. This objective of this assessment was calculated the fertilizer subsidy through the distribution cost subsidy calculation method for 2004 compare to government fertilizer subsidy budget for 2004, Rap. 1.3 trillion. The result showed in 2004 the government had to budgeted about Rp. 1.64 trillion for fertilizer subsidy. In the other calculation using 2004 distribution cost and fee for distributor, the fertilizer subsidy increased to Rp. 1.875 trillion. This calculation bigger than the government fertilizer subsidy budget for 2004. It is necessary to reallocate the government budget for fertilizer subsidy and stabilized exchange rate for stabilizing fertilizer production and price at farmer level.
Keywords: Fertilizer Subsidy, Cost Distribution, Exchange Rate, Highest Fertilizer Price